The role of the practice nurse in cancer care reviews. (2nd June 2021) - Dyer, Sandra
Abstract : Recent changes to the Quality and Outcomes Framework provide an ideal opportunity to improve the quality of cancer care reviews and cancer patients' experiences. Sandra Dyer explains the important role practice nurses can play in improving care Improved outcomes for people diagnosed with cancer have led to increasing numbers of people living with and beyond the disease, and for many, cancer has transitioned to a long-term condition. There is a greater need for models of care that best meet these patients' needs, with the role of primary care becoming increasingly important. Recent changes to the Quality and Outcomes Framework (QOF) provide an ideal opportunity to improve the quality of cancer care reviews and improve cancer patients' experiences. More education and training for general practice nurses on cancer is urgently required to allow them to lead on quality improvement in this important area of care.